An effective approach for identifying defective critical fabrication path. Issue 1 (1st January 2019) - Taha, Kamal
Abstract: Most defect signatures on wafers are caused by faulty tools. If these defects are not captured by in-line inspection tools or sampled during Defect Review-SEM, they are carried over multiple processing steps and discovered at the end of the fabrication procedure. Wafers with different defect signatures discovered at the end of the fabrication procedure are, most often, processed through same faulty tools. The fabrication paths of most defective wafers converge at some point to form a common sub-path before they disperse again. Usually, faulty tools in this common path cause most of the different defect signatures discovered at the end of the fabrication procedure. Process engineers would need to trace in reverse the fabrication paths to identify this common path to repair its tools. We introduce in this paper a defect diagnostic system called IDFP that can identify the common fabrication path that caused most of the defectivities on wafers discovered at the end of the fabrication procedure. We evaluated the quality of IDFP by experimentally comparing it with two systems. Results revealed marked improvement.